Substitution Effect of Rice Bran with Coffee Pulp Meal on Feed Efficiency and Percentages of Viscera Organs of Broilers - Betty Bagau; Meity Revonni Imbar; Florencia Nery Sompie; Fenny Rinai Wolayan; Youdhie Hanna Siriously Kowel (Buletin Peternakan, 2023)
Research on animal feed has often focused on finding alternative feed ingredients to replace conventional ones in order to reduce feed costs. By-products from processing crops and food products have received much attention as feed alternatives because of their consistent and mass production, one of them is a waste of coffee. This research was conducted to evaluate the substitution effect of rice bran with coffee pulp meal on feed efficiency and viscera organs of broiler. The 100 broilers (Hubbard strain) and placed randomly into 4 treatments (R0 = ration with rice bran 21% + 0% coffee pulp meal; R1 = ration with 14% rice bran + 7% coffee pulp meal; R2 = ration with 7% rice bran + 14% coffee pulp meal; R3 = ration with 0% rice bran + 21% coffee pulp meal and each treatment consisted of 5 replications, five broilers each. The broilers were arranged by completely randomized design; a Tukey test was used to compare mean different of the treatments. Substitution effect of Rice Bran with Coffee Pulp Meal on ration had significant effect on decreasing feed efficiency and significantly increase the weight percentage of heart, gizzard, pancreas, and intestine (P<0.05) but had no significant on the weight percentage of caecum in broiler (P>0.05) Tukey test showed that the higher proportion of coffee hull meal the feed consumption and body gain non-significant to R0, R1 and R2. On the other hand feed efficiency of R3 significantly lower compared to R0, R1and R2. The higher the percentage of liver, gizzard, pancreas and intestine weight. However, there was no significant effect on caecum weight percentage. The conclution was: Utilization coffee pulp meal had significant effect on decreasing feed efficiency and significantly increase the weight percentage of heart, gizzard, pancreas, and intestine